Depth-associated patterns in the development of benthic assemblages on artificial substrata deployed on shallow, subtropical reefs - Rule, Michael J.; Smith, Stephen D.A. (Journal of experimental marine biology and ecology, 2007)
Changes in the structure of many benthic habitats occur across a number of physical gradients and result in corresponding changes in the structure of associated epifaunal assemblages; however, investigations of faunal assemblages are often confounded by variation in the morphology of habitats. In this experiment, identical nests of nylon pan scourers were employed to examine changes in the structure of epifaunal assemblages across a depth gradient at two island sites within the Solitary Islands Marine Park (SIMP), NSW, Australia. Artificial substratum units (ASUs) were anchored to rocky reef at 8, 16 and 24 m for a period of five months over summer and winter. Data were subjected to univariate and multivariate statistical analyses to determine the similarity of assemblages across Depths, Islands and Times. A number of species displayed a distinct fidelity with depth across both islands and times. Although significant interactions between factors were apparent for most variables, very few significant differences across the main effects were identified for univariate analyses of summary community variables ( S, N, H′), major taxonomic groups (bivalves, amphipods, polychaetes) or individual species analysed. In contrast, multivariate analyses revealed significant differences in assemblage structure for all comparisons of depth during each sampling period. Although the experiment was conducted both over summer and again over winter, depth-associated patterns were maintained at each island during each sampling period. The results highlight the importance of depth as a structuring factor for epifaunal assemblages of subtropical rocky reefs.